Minha casa, minha luta: o MTST frente a ofensiva neoliberal - Campos, Marcos (2018)
In the process of capitalist accumulation there is a fundamental law: accumulation of wealth on the one hand in the hands of few owners, and on the other hand, the condition of misery for an enormous number of workers. The most precarious workers, most marginalized in this process, constitute a specific fraction of the working class, a huge reserve army ready to be absorbed by capital when it needs more workers. In Latin America and its dependent economy countries, this army is constituted not as a labor force to be called in the moments of capital expansion, but in fact makes up a large part of the working class, making marginality and precarity a rule and condition of workers in these countries. Studying the working class in Brazil, it goes through analyzing this segment, in particular to note to what extent neoliberal policies have thickened the ranks of the Brazilian reserve army. With the rise of Luis Inácio Lula da Silva as the presidency of the Republic, and with the neodevelopmentalist policies that came mainly from his second term, this fraction of class was also strongly impacted. The discussion about the role of such a fraction in the Brazilian political scenario appears again, with some authors pointing to its incapacity to organize and populist relationship with the PT governments, while other authors see in it new forms of struggle of the working class. It is in this sense that the study on one of the most important social movements of the current Brazilian conjuncture, the MTST, aims to contribute, seeking to reveal the socioeconomic characteristics of this fraction, as it was affected by the neoliberal period in Brazil, especially as housing policies dialogue with their condition and how a social movement can respond to such a scenario.